Health information seeking patterns among medical and non-medical university students in Egypt - Sabry, Hend Aly; Ezzat, Farah Mohamed; Salem, Marwa Rashad (Intelektual Pustaka Media Utama, 2023)
The researchers conducted the study to define university students’ current patterns of health information resources use, compare, and assess the resources medical and non-medical university students use when exercising health information seeking (HIS), and to assess their perceptions and behaviors regarding adoption of online tools. This is an exploratory cross- sectional study conducted among a convenience sample of 336 university students via an online survey comprised of the following: demographics, perspectives of health information seeking, and experiences and problems towards HIS. More than two thirds of the sampled students stated that they sought health information. Their most curious subject was lack of physical activity. Searching the internet and using social media were the most used ways to obtain health information. Ease of access and reliability of source were the most affecting sources while searching. Medical students prefer reliable websites in the health domain with high level of quality and credibility. While non-medical students access health information more through social media. Workshops could be organized for medical students to convey to them the proper criteria for selecting credible health websites sources. As regards non-medical students, reliable easily accessible health information sources that could be reached through social media.